GROWTH AND CHARACTERIZATION OF ZnS NANOPARTICLE - ., Motlan; Sirait, Makmur (JURNAL PENELITIAN SAINTIKA, 2013)
ZnS nanoparticle has been syntesized from zinc asetat and thiorea 0.2 M using copresipitation method. The structure of the ZnS nanoparticle are wurtzite with hexagonal and blende (sphalerit) with cubic shape with average size of 39.56 nm. The elements of the ZnS measuring using EDS it was found that Zn has a mass of sebesar 52.20% with disperse energy of 8.630 keV and S element of 18.92% with disperse energy of 2.307 keV